Chemical control of Cyperus rotundus in pre and post emergent application - Siqueira, Danyele Rodrigues; Alves, Rafaela Thais Benedito; Oliveira, Alax Andrade de; Vieira, Leonardo; Gabe, Jéssica Thais; Silva, Marcelo Rodrigo da; Guilherme, Denilson de Oliveira (Bionorte, 2022)
Objective: the objective of this work was to test potential herbicides, tested in a single dose of each commercial product as indicated in the package insert. Materials and Methods: the experiment was carried out in two trials, pre- and post-emergent, in a completely randomized block design with eight treatments and three replications in an 8x3 factorial scheme. The test was carried out in a BOD oven at 25º and 12 hours/light photoperiod in sand beds containing sedge rhizomes, visual evaluations were performed 7 and 14 days after herbicide application, in both tests, followed by a tretrazolium test at the end. of visual evaluation in tubers that did not germinate, thirty days after pre-emergent application. Results: the most efficient control was the herbicide of the Organoarsenic group (MSMA) which presented 0.67% of viable rhizomes in the pre-emergent assay and 0.33% of viable rhizomes in the post-emergent assay. Conclusion: the herbicide of the organoarsenic chemical group (MSMA) was the most efficient for the control of nutsedge in both trials. The herbicides ethoxysulforan and glyphosate showed control efficiency in the post-emergence assay.